2017
DOI: 10.4172/2168-9784.1000261
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Malaria Test Preference among Households in Rubavu District, Rwanda: A Cross-sectional Study

Abstract: Background: If people are not diagnosed and treated promptly for malaria, they may develop severe complications and death. Globally, an estimated 3.3 billion people are at risk of being infected with malaria and 1.2 billion are at high risk. The World Health Organization recommends using malaria rapid diagnostic tests (RDTs) or microscopy followed by prescribing antimalarial only to patients who have a positive test result. In Rwanda, malaria RDT was introduced in 2008 to be used by community health workers (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In 2008, the Rwanda Ministry of Health (MOH) piloted and scaled up the mRDTs (by community health workers) as recommended by WHO's Roll Back Malaria program (source) in most of the regions as a way to expand and strengthen malaria diagnostic capacity throughout the country (22). In Rwanda, community health workers (CHWs) are the rst point of contact with healthcare services for those with fever or a history of fever.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2008, the Rwanda Ministry of Health (MOH) piloted and scaled up the mRDTs (by community health workers) as recommended by WHO's Roll Back Malaria program (source) in most of the regions as a way to expand and strengthen malaria diagnostic capacity throughout the country (22). In Rwanda, community health workers (CHWs) are the rst point of contact with healthcare services for those with fever or a history of fever.…”
Section: Introductionmentioning
confidence: 99%
“…This was a cross-sectional prospective study. All patients self-reported to CHWs for malaria diagnosis from 22 April to 08 July 2021 in Ngoma district who were willing to participate in this study were included. Patients who had recovered from malaria within the past three weeks were not included in this study because it was revealed that malaria antigen can be found in blood for 3 weeks after completion of treatment, which could increase false positive results (17).…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, the Rwanda Ministry of Health (MOH) piloted and scaled up the mRDTs (by community health workers) as recommended by WHO's Roll Back Malaria program (source) in most of the regions as a way to expand and strengthen malaria diagnostic capacity throughout the country [22]. In Rwanda, community health workers (CHWs) are the first point of contact with healthcare services for those with fever or a history of fever.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008,the Rwanda Ministry of Health (MOH) piloted and scaled up the mRDTs (by community health workers) as recommended by WHO's Roll Back Malaria program (source) in the most of the regions as a way to expand and strengthen malaria diagnostic capacity throughout the country (22). In Rwanda, Community health workers (CHWs) are the rst point of contact with healthcare services for those with fever or a history of fever.…”
Section: Introductionmentioning
confidence: 99%